Sejarah Mushaf Al-Qur’an Standar Braille Penelusuran Awal - Yunardi, Ecep Badri (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
The birth of the Quranic Mushaf in Braille Standard requires a long process and involves many parties, especially the Qur'anic scholars and experts in related fields. This writing try to reveal the dynamics that emerge and developes relating to the guideline which becomes the standard in the writing of this Mushaf. One of the crucial issues being emerged is concerning the use ofÃ‚Â rasm to be used as a reference, whether usmani orÃ‚Â imlaÃ¢â‚¬â„¢i. In addition, this writing also describes the birth of the Qur'an in Braille Standards chronologically from several processes of working meetings organized by the Ministry of Religious Affairs.